Formulasi dan Evaluasi Sediaan Gel Moisturizer Dari Ekstrak Buah Nanas (Ananas comosus (L.) Merr) dengan Variasi Konsentrasi - Rada Angelina Putri; Rustam T; Wahyuni L. Ode (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Guava Pineapple (Ananas comosus (L.) Merr.) contains vitamin C, flavonoids, phenolic compounds, and bromelain, which have the potential to be used in cosmetic preparations. This study aimed to formulate pineapple extract into a moisturizing gel and evaluate the physical characteristics of the resulting preparation. The pineapple extract was formulated in three formulas with concentrations of 5%, 10%, and 15%. The resulting formulations were evaluated for organoleptic properties, homogeneity, pH, spreadability, adhesion, irritation, and stability. The results showed that all formulas met the physical evaluation requirements. The formulation was a semi-solid, homogeneous gel with a pH of 5, a spreadability of 5.2–5.8 cm, an adhesion of 4.2–5.1 seconds, non-irritating, and stable during storage. The conclusion of this study is that pineapple (Ananas comosus (L.) Merr.) extract can be formulated into a moisturizing gel that meets the physical quality requirements of the preparation.